1996
DOI: 10.1006/dbio.1996.0074
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Protein Regulated during the Transition from Active to Quiescent Phenotype in Cultured Endothelial Cells

Abstract: Pigpen is a 67-kDa Sepharose-binding molecule isolated from mammalian endothelial and retinal pigmented epithelial cells. The protein is distributed nonhomogeneously in the nucleus, exhibiting diffuse staining throughout (excluding nucleoli), together with a small number of intensely stained focal points, or granules, and punctate staining along the nuclear envelope. Pigpen was absent or greatly attenuated in the nonepithelial cell types we examined, including fibroblasts, myeloma, and astroglia. cDNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 1 publication
4
33
0
1
Order By: Relevance
“…Importantly, it was recently shown that pigpen is highly expressed in rat brain tumor microvessels but is absent in mature brain vasculature, even in zones immediately adjacent to the tumor (7). Together with other observations on the up-regulation of pigpen in wounded vascular cell monolayers (5,7,8), these data suggest that pigpen's expression pattern underlies a functional role in regulating EC phenotype.We tested the hypothesis that pigpen is important for cell division by microinjection of anti-pigpen Fab fragments into the nuclei of EC in proliferating cultures. More than 200 individual cells were injected, tracked, and assayed for progression through mitosis.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Importantly, it was recently shown that pigpen is highly expressed in rat brain tumor microvessels but is absent in mature brain vasculature, even in zones immediately adjacent to the tumor (7). Together with other observations on the up-regulation of pigpen in wounded vascular cell monolayers (5,7,8), these data suggest that pigpen's expression pattern underlies a functional role in regulating EC phenotype.We tested the hypothesis that pigpen is important for cell division by microinjection of anti-pigpen Fab fragments into the nuclei of EC in proliferating cultures. More than 200 individual cells were injected, tracked, and assayed for progression through mitosis.…”
supporting
confidence: 79%
“…Importantly, it was recently shown that pigpen is highly expressed in rat brain tumor microvessels but is absent in mature brain vasculature, even in zones immediately adjacent to the tumor (7). Together with other observations on the up-regulation of pigpen in wounded vascular cell monolayers (5,7,8), these data suggest that pigpen's expression pattern underlies a functional role in regulating EC phenotype.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Trp53 is commonly mutated in cancers and elevated protein levels are believed to result from post-translational stabilization (Kubbutat et al, 1997); our study reveals increased mRNA levels of this developmentally regulated gene. Tls/Fus [also called pigpen in the mouse (Alliegro and Alliegro, 1996)] is a recurring target of chromosomal translocation in human myxoid liposarcoma (Rabbitts et al, 1993), where its pathogenic mechanisms are unclear.…”
Section: Significance Of Transcripts That Decline In Abundance With Pmentioning
confidence: 99%
“…Interestingly, 3 of the 4 RNA-binding proteins in our collection have been previously implicated in stem cell maintenance: pumilio controls germline stem cells in C. elegans and Drosophila (Crittenden et al, 2002), pigpen expression correlates with undifferentiated, proliferative endothelial cells (Alliegro and Alliegro, 1996;Alliegro, 2001), and dyskerin is a component of telomerase that appears to be essential for stem cell renewal Molecular profile of neural crest precursors in a variety of tissues including the basal layer of the epidermis (reviewed by Marcinian et al, 2000). Since the neural crest is a multipotent stem cell population, these proteins are obvious candidates for post-transcriptional maintenance of the undifferentiated, stem cell state of neural crest cells as well.…”
Section: Post-transcriptional and Post-translational Regulation Of Nementioning
confidence: 99%